Sociolinguistic analysis of code mixing and code switching in Nessie Judge and Cinta Laura's “Glitch in the Matrix” YouTube video - Qutratu'ain, Dita Shafa; Yuliano, Siti Annisa; Ersa, Moch.; Degaf, Agwin (Jurnal Langua, 2024)
This research explores the use of code-mixing and code-switching in the YouTube collaboration video "Glitch in the Matrix" by Nessie Judge and Cinta Laura. The study aims to provide a comprehensive examination of these linguistic phenomena within the specific context of the video. Employing qualitative methods and a sociolinguistic approach, the research demonstrates that code-mixing and code-switching are natural occurrences among multilingual speakers. Data were collected through systematic observation, categorization, and analysis of the video content. Nessie Judge and Cinta Laura, both multilingual individuals, serve as the subjects of this study due to their frequent use of code-mixing and code-switching. The findings reveal numerous instances of code-mixing, including the integration of English words into Indonesian phrases and the introduction of English phrases into Indonesian discourse. The study also identified various types of code-mixing: inner code-mixing, outer code-mixing, and hybrid code-mixing. Regarding code-switching, language alternation was observed with specific reasons or purposes, classified based on the direction of the switch, either from English to Indonesian or from Indonesian to English. The analysis utilized the theoretical framework of Criper and Widdowson (1975), which provided a foundation for understanding the sociolinguistic dimensions of these phenomena.